(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The COVID-19 pandemic was a one of its kind pandemics that shook the world, including various sectors such as healthcare, education, tourism, retail, and hospitality. This research paper aims to provide an analysis of the literature that has been published on the impact of COVID-19covering the different sectors, using data and statistics from reputable sources like Statista. The paper begins with an introduction to the pandemic and its global impact, followed by a literature review of the effects on each sector. The review highlights the challenges faced by each sector, such as revenue losses, job cuts, and the shift towards online and digital platforms. The paper concludes by discussing the long-term implications of the pandemic on these sectors and the need for strategic planning to mitigate the effect.